2020
DOI: 10.1002/cbic.201900609
|View full text |Cite
|
Sign up to set email alerts
|

Targetable Tetrazine‐Based Dynamic Nuclear Polarization Agents for Biological Systems

Abstract: Dynamic nuclear polarization (DNP) has shown great promise as a tool to enhance the nuclear magnetic resonance signals of proteins in the cellular environment. As sensitivity increases, the ability to select and efficiently polarize a specific macromolecule over the cellular background has become desirable. Herein, we address this need and present a tetrazine‐based DNP agent that can be targeted selectively to proteins containing the unnatural amino acid (UAA) norbornene‐lysine. This UAA can be introduced effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
(67 reference statements)
0
26
0
Order By: Relevance
“…The major drawback of amber suppression for MAS NMR studies of chromatin is that it results in much lower yields of the desired protein, a situation that can be severely exacerbated under isotopic labeling conditions. Nevertheless, we have successfully used this technique to introduce UAAs in different isotopically labeled proteins, including some that are relevant for chromatin studies ( Lim et al, 2020 ).…”
Section: Chemical Biology Tools For Mas Nmr Of Modified Chromatin Samplesmentioning
confidence: 99%
“…The major drawback of amber suppression for MAS NMR studies of chromatin is that it results in much lower yields of the desired protein, a situation that can be severely exacerbated under isotopic labeling conditions. Nevertheless, we have successfully used this technique to introduce UAAs in different isotopically labeled proteins, including some that are relevant for chromatin studies ( Lim et al, 2020 ).…”
Section: Chemical Biology Tools For Mas Nmr Of Modified Chromatin Samplesmentioning
confidence: 99%
“… 87,88 In the context of DNP experiments, Debelouchina and coworkers have reported the first successful example of targetable tetrazine-based PAs for biological systems. 75 In their work, the unnatural amino acid norbornene-lysine is introduced in the protein sequence through amber suppression. 85 DNP spin labeling is then obtained through biorthogonal conjugation of a TOTAPOL-tetrazine radical (TTz) as illustrated in Fig.…”
Section: Targeting Strategiesmentioning
confidence: 99%
“…More recently, the Debelouchina group demonstrated the first use of bioorthogonal chemistry in the context of t DNP experiments as described above. 75 Their approach was first tested on three purified mutant proteins (ubiquitin, heterochromatin protein HP1α, and the structural maintenance of chromosomes protein SMC) at concentrations of only tens of μM. As a proof of concept, t DNP using the tetrazine-based PA was then applied to isotopically labeled bacterial lysates containing overexpressed ubiquitin mutants without purification.…”
Section: Targeted Dnp For In-cell Nmr: Improving Selectivity In Complex Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, advancements in radical development could further reduce intracellular protein concentrations than can be studied by DNP‐ssNMR methods. In a similar vein, taggable radicals that would irreversibly conjugate to the proteins of interest harboring an inert unnatural amino acid have recently been developed . In complex and heterogeneous biological environments, it has already been shown that tagging the DNP agents directly to the protein of interest is advantageous in obtaining molecule‐specific DNP enhancements …”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%